Kandungan Flavonoid Total dan Aktivitas Antioksidan dari Ekstrak Polaritas yang Berbeda dari Daun Pereskia bleo - Nayaka, Ni Made Dwi Mara Widyani; Cahyaningsih, Erna; Sasadara, Maria Malida Vernandes; Yuda, Putu Era Sandhi Kusuma; Indriani, Felia Riska (Jurnal Ilmiah Medicamento, 2023)
Antioxidant agents are essential for the body due to its ability to scavenge free radicals. Medicinal plants contain phytochemicals that act as antioxidants. The current research aimed to determine the total flavonoid content (TFC) and antioxidant activity of Pereskia bleo leaves extracts from various solvents with different polarities. The nonpolar solvent (n-hexane) was used as the first step of extraction and its residues were then macerated using semi-polar (ethyl acetate) and polar (ethanol 96%) solvents consecutively. The TFC was determined using the colorimetric method while antioxidant activity was examined through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Antioxidant activity was presented as Inhibitory Concentration 50 (IC50) and Antioxidant Activity Index (AAI). It is noticeable that among analyzed extracts, the ethyl acetate extract of P. bleo leaves contained the highest flavonoid content (15.052 ± 0.172 g quercetin equivalent/100 g extract). Furthermore, the greatest antioxidant activity was obtained from n-hexane extract with the value of IC50 and AAI being 217.307 ppm and 0.230, respectively. Pearson coefficient correlation (r) between TFC and AAI was -0.106. The current study concluded that P. bleo leaves extracts using solvents with different polarities showed variation in TFC values and antioxidant activity. Moreover, TFC was not the main contributor to the antioxidant activity of P. bleo leaves extracts.